Balancing reserves within a decarbonized European electricity system in 2050: From market developments to model insights - Casimir Lorenz (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper expands the discussion about future balancing reserve provision to the long-term perspective of 2050. Most pathways for a transformation towards a decarbonized electricity sector rely on very high shares of fluctuating renewables. This can be a challenge for the provision of balancing reserves, although their influence on the balancing cost is unclear. Apart from the transformation of the generation portfolio, various technical and regulatory developments within the balancing framework might further influence balancing costs: i) dynamic dimensioning of balancing reserves, ii) provision by fluctuating renewables or new (battery) storage technologies, and iii) exchange of balancing reserves between balancing zones. The first part of this paper discusses and transforms these developments into quantitative scenario definitions. The second part applies these scenarios to dynELMOD (dynamic Electricity Model), an investment model of the European electricity system that is extended to include balancing reserve provision. In contrast to other models applied in most papers on balancing reserves, this model is capable of evaluating the interdependencies between developments in balancing reserve provision and high shares of fluctuating renewables jointly. The results show that balancing reserve cost can be kept at current levels for a renewable electricity system until 2050, when using a dynamic reserve sizing horizon. Apart from the sizing horizon, storage capacity withholding duration and additional balancing demand from RES are the main driver of balancing costs. Renewables participation in balancing provision is mainly important for negative reserves, while storages play an important role for the provision of positive reserves. However, only on very few occasions, additional storage investments are required for balancing reserve provision, as most of the time sufficient storage capacities are available in the electricity system.
Keywords: Q42; Q47; Q48; C61; L94; 330; balancing reserves; electricity sector modeling; investment model; renewable participation; cross-border cooperation; dynamic sizing